Graph Neural Networks for Heart Failure Prediction on an EHR-Based Patient Similarity Graph - Boll, Heloisa Oss; Byttner, Stefan; Recamonde-Mendoza, Mariana (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais Estendidos do XXV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2025.7013, 2025)
Accurate disease prediction is critical in healthcare. This study introduces Graph Neural Networks (GNNs) and Graph Transformer (GT) models to predict heart failure (HF) incidence at the next hospital visit using a patient similarity graph. Using MIMIC-III Electronic Health Records (EHR) data, we constructed a patient similarity graph via K-Nearest Neighbors (KNN) with embeddings from diagnoses, procedures, and medications. We implemented GraphSAGE, GAT, and GT to predict HF, evaluating performance with F1, AUROC, and AUPRC metrics against baseline models. A three-axed interpretability analysis explored model decision-making. GT achieved the highest performance (F1: 0.5361, AUROC: 0.7925, AUPRC: 0.5168). While Random Forest (RF) showed a similar AUPRC, GT provided superior interpretability by leveraging patient relational information. Analyzing attention weights, graph structure, and clinical features offered deeper insights into classification decisions.